Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675155
|View full text |Cite
|
Sign up to set email alerts
|

Is It Good to Be Like Wikipedia?

Abstract: Online question and answer (Q&A) sites, which are platforms for users to post and answer questions on a wide range of topics, are becoming large repositories of valuable knowledge and important to societies. In order to sustain success, Q&A sites face the challenges of ensuring content quality and encouraging user contributions. This paper examines a particular design decision in Q&A sitesallowing Wikipedia-like collaborative editing on questions and answers, and explores its beneficial effects on content qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Fourth, we examined the question–answer interaction and asker acceptance rates to identify any potential information gaps that were not addressed by the Q&A community. These criteria were used in previous research to evaluate how questions were addressed on social Q&A websites (Burghardt et al, 2017; Jin et al, 2017; Li et al, 2015; Sin et al, 2016; Teevan et al, 2011; Tian et al, 2013). The question–answer interaction rate was defined as the ratio of the number of answers on each topic (dependent variable) to the popularity of questions, represented by the question view count on each topic (independent variable) (Borghol et al, 2012; Sin et al, 2016; Szabo & Huberman, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, we examined the question–answer interaction and asker acceptance rates to identify any potential information gaps that were not addressed by the Q&A community. These criteria were used in previous research to evaluate how questions were addressed on social Q&A websites (Burghardt et al, 2017; Jin et al, 2017; Li et al, 2015; Sin et al, 2016; Teevan et al, 2011; Tian et al, 2013). The question–answer interaction rate was defined as the ratio of the number of answers on each topic (dependent variable) to the popularity of questions, represented by the question view count on each topic (independent variable) (Borghol et al, 2012; Sin et al, 2016; Szabo & Huberman, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Negative binomial regression (nbreg) models are used to model count outcome variables with great variability ( Cameron & Trivedi, 2013 ) and have been applied in different social computing tasks (Q. Chen et al, 2020 ; G. Li et al, 2015 ). Considering the over-dispersed distribution of all engagement dimensions as shown in Table 2 , we adopted nbreg model to estimate the impact of content topic, emotion valence, video category and government-citizen collaboration on youth engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Collaboration in content generation, as a common practice in social media websites, has been proved to be beneficial in enhancing content quality and engaging social media users. For instance, Li et al found that collaborative editing in Stack Overflow increased the number of positive votes by 181% for the questions and 119% for the answers (G. Li, Zhu, Lu, Ding, & Gu, 2015 ). During times of crisis, government-citizen collaboration could further fill the information gap between government and citizens, and thus serve as a significant approach to facilitate information sharing ( Pipek, Liu, & Kerne, 2014 ).…”
Section: Theoretical Foundations and Hypothesismentioning
confidence: 99%
“…The finding also showed that malpractices such as plagiarism were also common on Stack Overflow. Li, Zhu, Lu, Ding, and Gu (2015) examined the data of editing behaviour extracted from Stack Overflow. Their analysis indicates that the benefits of collaborative editing outweigh its negative effect.…”
Section: Related Workmentioning
confidence: 99%